2010
DOI: 10.1007/s10714-010-1092-3
|View full text |Cite
|
Sign up to set email alerts
|

A Weyl-Dirac cosmological model with DM and DE

Abstract: In the Weyl-Dirac (W-D) framework a spatially closed cosmological model is considered. It is assumed that the space-time of the universe has a chaotic Weylian microstructure but is described on a large scale by Riemannian geometry. Locally fields of the Weyl connection vector act as creators of massive bosons having spin 1. It is suggested that these bosons, called weylons, provide most of the dark matter in the universe. At the beginning the universe is a spherically symmetric geometric entity without matter.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
(25 reference statements)
0
18
0
Order By: Relevance
“…For readable and pedagogical introduction to WG we recommend the classical books [22], [23], and [24], however research papers can be found where the subject is exposed in a more or less pedagogical way [25][26][27][28]. It has to be said that, although there was a moderate revival of Weyl's ideas after Dirac's "large numbers hypothesis" [29] (see also [30]), in the last decades there has been a renewed interest in WG [27,28,[31][32][33][34][35][36][37], in connection to the search for alternative explanations to outstanding questions of fundamental physics, such as the dark matter/dark energy issues. A Weyl space (M, g µν , w µ ), is a manifold M endowed with a metric g µν and a (gauge) vector field w µ , so that the following "metricity" condition is satisfied:…”
Section: Fundamentals Of Weyl Geometrymentioning
confidence: 99%
See 3 more Smart Citations
“…For readable and pedagogical introduction to WG we recommend the classical books [22], [23], and [24], however research papers can be found where the subject is exposed in a more or less pedagogical way [25][26][27][28]. It has to be said that, although there was a moderate revival of Weyl's ideas after Dirac's "large numbers hypothesis" [29] (see also [30]), in the last decades there has been a renewed interest in WG [27,28,[31][32][33][34][35][36][37], in connection to the search for alternative explanations to outstanding questions of fundamental physics, such as the dark matter/dark energy issues. A Weyl space (M, g µν , w µ ), is a manifold M endowed with a metric g µν and a (gauge) vector field w µ , so that the following "metricity" condition is satisfied:…”
Section: Fundamentals Of Weyl Geometrymentioning
confidence: 99%
“…This is to be contrasted with vacuum BD theory where this is a mirage or spurious symmetry instead. Put in different words: in the gravitational theory depicted by (35), (36), the laws of gravity look the same in the different conformal frames, while the spacetime coincidences -properly the observations -are unchanged. This is an outstanding example of a theory where, unlike BD theory, the different conformal descriptions of a given phenomenon are actually (physically and mathematically) equivalent.…”
Section: Conformal Equivalence Principlementioning
confidence: 99%
See 2 more Smart Citations
“…This implies that one has the freedom to choose the unit length at each point, which is the Weyl gauge freedom [1]. A variety of works have been done in the Weyl geometry including the cosmology [2], relations to scalar-tensor [3] and teleparallel theories [4]. One can also restrict the form of Weyl vector to be a derivative of a scalar as w µ = ∂ µ φ [5].…”
Section: Introductionmentioning
confidence: 99%